Pengaruh Kandungan Protein Ransum yang Berbeda terhadap Kecernaan dan Fermentabilitas Rumen Sapi Perah secara In vitro: The Effect of Different Feed Protein Content on Digestibility and Fermentability of Dairy Rumen using In vitro - Rika Zahera; Dian Anggraeni; Zikri Aulia Rahman; Dwierra Evvyernie (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2020)
The most of protein requirement for cows is fulfilled by microbial protein. Increasing the protein from ration usually influences the milk production in dairy cows. However, the availability of dietary protein should support rumen ecosystem through microbial activity in the fermentation and digestion process. The aim of this study was to evaluate the protein levels of dairy cow ration on the rumen fermentability and digestibility using an in vitro method. Randomized block design with three levels of protein ration as a treatment and three times taken of rumen liquor as a block. The treatments were: R1= ration with low protein; R2= ration with moderate protein and R3= ration with high protein. The measured parameters were rumen fermentability (total VFA, N-NH3 and pH), in vitro dry matter digestibility (IVDMD) and in vitro organic matter digestibility (IVOMD). The results showed that there were significantly increase in dry and organic matter digestibility (p<0.05), due to increasing the level of dietary protein, but there was no effect in the fermentability, except a slight increase in N-NH3 concentration. The conclusion of this study was the highest level of protein ration enhances the digestibility, and showed a tendency for higher N-NH3. Key words: dairy cattle, dietary protein, digestibility, fermentability, in vitro DAFTAR PUSTAKA [Ditjennak-Keswan] Direktorat Jendral Peternakan dan Kesehatan Hewan. 2019. Pemerintah dorong perbaikan kualitas dan kuantitas susu nasional [internet]. Tersedia pada: http://ditjennak.pertanian.go.id/pemerintah-dorong-perbaikan-kualitas-dan-kuantitas-susu-nasional Anggraeny YN, Soetanto H, Kusmartono & Hartutik. 2015. Sinkronisasi suplai protein dan energi dalam rumen untuk meningkatkan efisiensi pakan berkualitas rendah. WARTAZOA. 25(3):107–116 Chanthakhoun V, Wanapat M & Berg J. 2012. Level of crude protein in concentrate supplements influenced rumen characteristics, microbial protein synthesis and digestibility in swamp buffaloes (Bubalus bubalis). Livestock Science. 144(3):197–204. Cherdthong A & Wanapat M. 2013. Manipulation of in vitro ruminal fermentation and digestibility by dried rumen digesta. Livestock Science. 153(1–3):94–100. Colmenero JJO & Broderick GA. 2006. Effect of dietary crude protein concentration on milk production and nitrogen utilization in lactating dairy cows. Journal of Dairy Science. 89(5):1704–1712. Conway E. 1957. Microdiffusion of Analysis of Association Official Analytical Chemist. Georgia (US): Georgia Press. Despal, Permana IG, Safarina SN & Tatra AJ. 2011. Penggunaan berbagai sumber karbohidrat terlarut air untuk meningkatkan kualitas silase daun rami. Media Peternakan. 34(2):69–76. Despal, Zahera R, Lestari DA, Ma’rifah H & Permana IG. 2015. Ketersediaan dan kualitas sumberdaya pakan musim kemarau dan dampaknya terhadap pemenuhan nutrien dan performa sapi perah di Pangalengan Kabupaten Bandung. Sumedang (ID): Seminar Nasional Peternakan Berkelanjutan, Universitas Pajajaran Dung DV, Shang W & Yao W. 2014. Effect of crude protein levels in concentrate and concentrate levels in diet on in vitro fermentation. Asian-Australasian Journal of Animal Science. 27(6):797–805. Forejtová J, Lád F, Třináctý J, Richter M, Gruber M, Doležal P, Homolka P & Pavelek L. 2005. Comparison of organic matter digestibility determined by in vivo and in vitro methods. Czeh Journal of Animal Science. 50(2):47–53. Hernaman I, Tarmidi AR & Dhalika T. 2017. Kecernaan in vitro ransum sapi perah berbasis jerami padi yang mengandung konsentrat yang difermentasi oleh Saccharomyces cerevisiae dan Effective Microorganisms-4 (EM-4). Majalah Ilmu Peternakan. 20(2):45–48. Holik YLA, Abdullah L & Karti PDMH. 2019. Evaluasi nutrisi silase kultivar baru tanaman sorgum (Sorghum bicolor) dengan penambahan legum Indigofera sp. pada taraf berbeda. Jurnal Ilmu Nutrisi dan Teknologi Pakan. 17(2):38–46. Imran M, Pasha TN, Shahid MQ, Babar I & Naveed M. 2017. Effect of increasing dietary metabolizable protein on nitrogen efficiency in Holstein dairy cows. Asian-Australasian Journal of Animal Science. 30(5):660–665. Joo JW, Bae GS, Min WK, Choi HS, Maeng WJ, Chung YH & Chang MB. 2005. Effect of protein sources on rumen microbial protein synthesis using rumen simulated continuous culture system. Asian-Australasian Journal of Animal Science. 18(3):326–331. Law RA, Young FJ, Patterson DC, Kilpatrick DJ, Wylie ARG & Mayne CS. 2009. Effect of dietary protein content on animal production and blood metabolites of dairy cows during lactation. Journal of Dairy Science. 92(3):1001–1012. Leonardi C, Stevenson M & Armentano LE. 2003. Effect of two levels of crude protein and methionine supplementation on performance of dairy cows. Journal of Dairy Science. 86(12):4033–4042. Lestari DA, Abdullah L & Despal. 2015. Comparative study of milk production and feed efficiency based on farmer best practices and National Research Council. Media Peternakan. 38(2): 110-117 McDonald P, Edwards R, Greenhalgh J, Morgan C, Sinclair L & Wilkinson R. 2010. Animal Nutrition. Seventh Ed. London (UK): Pearson Education McMurphy C, Duff G, Sanders S, Cuneo S & Chirase N. 2011. Effects of supplementing humates on rumen fermentation in Holstein steers. South Asian-Australasian Journal of Animal Science. 41(2):134–140. Nadeau E, Englund J & Gustafsson AH. 2007. Nitrogen efficiency of dairy cows as affected by diet and milk yield. Livestock Science. 111(1–2):45–56. NRC. 1978. Nutrient Requirements of Dairy Cattle. 5th Revised Ed. Washington (US): National Academy Press. NRC. 2001. Nutrient Requirement of Dairy Cattle. 7th Revised Ed Washington (US): National Academy Press Permana IG, Despal, Zahera R & Damayanti E. 2017. Evaluasi kecukupan nutrien, produksi dan kualitas susu sapi perah di peternakan rakyat. Bogor (ID): Seminar Nasional Industri Peternakan, Fakultas Peternakan IPB. Saha S, Gallo L, Bittante G, Schiavon S, Bergamaschi M, Gianesella M & Fiore E. 2019. Rumination time and yield, composition, lactating holstein cows. Animals. 9(2):1–13. Shahzad MA, Tauqir NA, Ahmad F, Nisa MU, Sarwar M & Tipu MA. 2011. Effects of feeding different dietary protein and energy levels on the performance of 12 – 15-month-old buffalo calves. Tropical Animal Health Production. 43(3):685–694. Sucak MG, Serbester U & Görgülü M. 2017. Effects of dietary starch and crude protein levels on milk production and composition of dairy cows fed high concentrate diet. Turkish Journal of Agriculture - Food Science and Technology. 5(6):563–567. Suharti S, Aliyah DN & Suryahadi. 2018. Karakteristik fermentasi rumen in vitro dengan penambahan sabun kalsium minyak nabati pada buffer yang berbeda. Jurnal Ilmu Nutrisi dan Teknologi Pakan. 16(3):56–64. Xia C, Aziz M, Rahman U, Yang H, Shao T, Qiu Q, Su H & Cao B. 2018. Effect of increased dietary crude protein levels on production performance, nitrogen utilization, blood metabolites and ruminal fermentation of Holstein bulls. Asian-Australasian Journal of Animal Science. 31(10):1643–1653. Zahera R, Permana IG & Despal. 2015. Utilization of mungbean’s greenhouse fodder and silage in the ration for lactating dairy cows. Media Peternakan. 38(2):123–131